+0  
 
0
226
1
avatar+3434 

Help.

NotSoSmart  Oct 23, 2017
 #1
avatar+89840 
+1

3x + 2y +  z  = 7     (1)

5x + 5y + 4z  = 3    (2)

3x + 2y + 3z  = 1    (3)

 

The object, NSS, is to eliminate a variable and end up with 2 equations with two unknowns

We can choose any variable that we want......here....z seems easiest

Multiply the first equation by -4  and add it to equation 2

 

-12x - 8y -  4z = -28

  5x  + 5y + 4z =   3

________________

  -7x - 3y          =  -25         →  7x + 3y = 25      (4)

 

 

Multiply the first equation by -3 and add it to to the 3rd equation

 

  -9x - 6y - 3z = -21

   3x  + 2y + 3z = 1

_________________

 - 6x - 4y      =  -20     →  6x + 4y  =  20    (5)

 

Multiply (4) by  4   and (5) by  -3

 

   28x +12 y = 100

 -18x -  12y  =  -60         add these together

 

10x =  40      divide both sides by 10

x = 4

 

Using (5) to find y, we have

6(4) + 4y = 20

24 + 4y  = 20    subtract24 from both sides

4y  = -4      divide both sides by 4

y = - 1

 

And using   3x  + 2y + 3z = 1  to find z, we have

 

3 (4) + 2 (-1) + 3z  = 1

12 - 2 + 3z  = 1

10 + 3z  = 1    subtract 10 from both sides

3z = -9       divide both sides by 

z = -3

 

So....{ x , y, z }  =  { 4, -1, -3 }

 

 

cool cool cool

CPhill  Oct 23, 2017

31 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.